Indocyanine-green-guided targeted laser photocoagulation of capillary macroaneurysms in macular oedema: a pilot study. Issue 2 (6th June 2016) - Paques, Michel; Philippakis, Elise; Bonnet, Clémence; Falah, Sabrina; Ayello-Scheer, Sarah; Zwillinger, Stéphanie; Girmens, Jean-François; Dupas, Benedicte
Abstract : Aims: In longstanding diabetic macular oedema (DME) or retinal vein occlusion (RVO), capillary macroaneurysms may develop. Indocyanine green angiography (ICGA) has been shown to optimise their detection. Here, we report the anatomical and functional outcome of the elective photocoagulation of capillary macroaneurysms. Methods: A retrospective, interventional, two-centre study. In eyes with chronic macular oedema and severe hard exsudates due to diabetic retinopathy or RVO, the presence of capillary macroaneurysms (defined by a diameter larger than 150 µm) was assessed by ICGA and optical coherence tomography (OCT). Capillary macroaneurysms were selectively photocoagulated, the presence of photothrombosis within the lumen being assessed by immediate OCT. Results: Four eyes from three patients with DME and five eyes from five patients with RVO were included. The median duration of visual loss was 4 years. Median initial visual acuity (VA) was 20/200. The median number of capillary macroaneurysms per eye was 2 (range, 1–8) and their median size was 410 µm (range, 154–603). Six months after photocoagulation, there was a significant reduction in macular thickness (mean±SD, 528 µm±200 vs 271 µm±152, p<0.05) and improvement of VA (mean log MAR, 0.82 vs 0.58, p<0.05). Conclusions: During macular oedema with severe hard exsudates due to DME or RVO, systematic detection of capillary macroaneurysms by ICGA followed by their OCT-controlled photocoagulation may be of interest. These results may contribute to re-evaluate the role of photocoagulation in the management of longstanding macular oedema.